Analysis Of Factors Affecting Competitive Advantage In Business Management - Arif Rohman Hakim*; Abi Surya Wijaya; Akhmad Syafi’i; Upit Elya Rohimi (Universitas Syiah Kuala, 2023)
The numerous forms of company competition in the world are making it more difficult year after year. The purpose of business management is to ensure that an organization is effectively run, survives, and performs better than before in an era of intense competition on a worldwide scale. Creating a competitive advantage is one of the goals of business management in maintaining corporate performance. The goal of this study is to examine the variables that affect superior business management. Using qualitative research techniques in this investigation. Using a literature study methodology, this study. Formulating the issue, gathering data, classifying data, presenting data, and making conclusions were the stages of the data analysis process. The study's findings indicate that pricing strategy, differentiation strategy (including product quality, delivery, and distribution strategy), and focus strategy (including dependability, product flexibility, volume flexibility, product variety, and recollection strategy) are factors that affect competitive advantage. The study's findings suggest that businesses might use them as a source of knowledge for boosting their competitive advantage in order to maintain their existence and improve performance.